2018
DOI: 10.1002/mdc3.12590
|View full text |Cite
|
Sign up to set email alerts
|

Nigrosome Imaging and Neuromelanin Sensitive MRI in Diagnostic Evaluation of Parkinsonism

Abstract: Background Recent developments in magnetic resonance imaging (MRI) techniques have offered new research opportunities to visualize in vivo substantia nigra pathology in Parkinson's disease (PD). This paper summarizes the main findings of nigrosome imaging and neuromelanin sensitive MRI studies in patients with PD and other parkinsonisms. Methods The PubMed database was searched from 2005 to 2017 using the following keywords: Parkinson's disease and parkinsonism, in combination with MRI, nigrosome, neuromelanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 47 publications
2
47
0
1
Order By: Relevance
“…Studies have confirmed that patients with PD have a significantly reduced NM signal in the SN and LC ( 20 , 37 , 37 , 39 41 ). These signal changes have been found to be correlated with the absorption values of the nigrostriatal dopamine transporter ( 42 ).…”
Section: Neuromelanin-sensitive Imagingmentioning
confidence: 90%
“…Studies have confirmed that patients with PD have a significantly reduced NM signal in the SN and LC ( 20 , 37 , 37 , 39 41 ). These signal changes have been found to be correlated with the absorption values of the nigrostriatal dopamine transporter ( 42 ).…”
Section: Neuromelanin-sensitive Imagingmentioning
confidence: 90%
“…Thus, the technique of MRI visualization of nigrosome-1 allows differentiating PD patients from health subjects even at the onset of the disease. However, some cases of atypical parkinsonism (MSA, PSP, and CBD) may be characterized by a similar pattern of the disappearance of the nigrosome-1 to PD [57][58][59].…”
Section: Instrumental Testsmentioning
confidence: 99%
“…Used for differentiating PD patients from healthy subjects, but not able to differentiate from some cases of atypical parkinsonism (MSA, PSP, and CBD) [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Clinical Testsmentioning
confidence: 99%
“…Martín-Bastida et al [34] found neuromelanin to correlate with disease duration and DAT with UPDRS motor score, concluding neuromelanin might reflect the underlying pathophysiological process, whereas DAT represents the functional state of the dopaminergic system [48]. Nigrosome imaging [49,50] using T2* and susceptibility weighted imaging MRI sequences could be another SN MR-biomarker of interest to combine with DAT imaging. Further validation of the appropriate reference tissue and attenuation correction methods for DAT imaging with the new PET-MRI systems, however, is needed [38,[51][52][53].…”
Section: Pet-mrimentioning
confidence: 99%